Pengaruh Variasi Kemiringan Front Wall Dan Perioda Gelombang Air Laut Terhadap Daya Udara Yang Dihasilkan Dan Efisiensi Pada Model Oscillating Water Column (Owc) Pembangkit Tenaga Gelombang - Alif Rahman Peldiansah Ismael; Nurul Iman Supardi; Angky Puspawan; Yovan Witanto; ASF Alqap (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Ocean wave energy is a renewable resource with significant potential for development in Indonesia, given its vast coastal areas. One technology for converting wave energy into usable power is the Oscillating Water Column (OWC) system. This system utilizes the vertical motion of seawater inside a chamber to generate airflow, which then drives a turbine to produce energy. This study aims to analyze the effect of oscillating column tilt angle and wave period variations on the energy conversion efficiency of an OWC model, and to determine the optimal tilt angle for maximum efficiency in converting wave power into air power. The research was conducted experimentally using a laboratory-scale OWC model measuring 1500 mm in length, 300 mm in width, and 500 mm in height. The oscillating column tilt angles tested were 0°, 35°, 40°, and 45°. Artificial waves were generated using a motor drive at 30 rpm, 40 rpm, and 50 rpm, producing wave periods of 2.1 seconds, 1.6 seconds, and 1.2 seconds, respectively. Measured parameters included air velocity, motor speed, wave period, wavelength, and wave height. Calculations determined wave power, air power, and system efficiency. Results show tilt angle and wave period significantly affect OWC efficiency, with the highest efficiency reaching 41.00% at 40° tilt and 1.6-second waves.